Teaching Learning through Interdisciplinary Approaches - Pun, Min (Crossing the Border: International Journal of Interdisciplinary Studies, 2017)
There are many benefits of using interdisciplinary approaches in teaching and learning. One of the goals of teaching and learning is helping students to develop insights, problem solving skills and self-confidence. The teachers can bring them to their classroom is interdisciplinary approaches are used in the teaching learning process. In this way, interdisciplinary approaches help students develop their cognitive abilities such as skills and mental processes, which are necessary to solve the problems. Crossing the Border: International Journal of Interdisciplinary Studies 5(2) 2017: 1-2